2013
DOI: 10.3348/kjr.2013.14.2.183
|View full text |Cite
|
Sign up to set email alerts
|

CT Venography for Deep Vein Thrombosis Using a Low Tube Voltage (100 kVp) Setting Could Increase Venous Enhancement and Reduce the Amount of Administered Iodine

Abstract: ObjectiveTo investigate the validity of the 100 kVp setting in CT venography (CTV) in the diagnosis of deep vein thrombosis (DVT), and to evaluate the feasibility of reducing the amount of administered iodine in this setting.Materials and MethodsAfter receiving the contrast medium (CM) of 2.0 mL/kg, 88 patients underwent CTV of the pelvis and lower extremities by using one of four protocols: Group A, 120 kVp setting and 370 mgI/mL CM; group B, 120 kVp and 300 mgI/mL; group C, 100 kVp and 370 mgI/mL; group D, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 30 publications
(49 reference statements)
1
27
0
Order By: Relevance
“…There were evidences that optimizing the procedure by reducing kVp from 140 to 100 would improve the quality of the image and consequently the diagnosis process. [ 24 25 ] The mean of kVp in this study were 109 and 101 for pregnant and postpartum women, respectively.…”
Section: Discussionmentioning
confidence: 67%
“…There were evidences that optimizing the procedure by reducing kVp from 140 to 100 would improve the quality of the image and consequently the diagnosis process. [ 24 25 ] The mean of kVp in this study were 109 and 101 for pregnant and postpartum women, respectively.…”
Section: Discussionmentioning
confidence: 67%
“…They concluded that lower tube voltage CTV protocol showed significantly higher venous enhancement and contrast to noise ratio and image noise similar to the conventional 120 kVp protocol in spite of administering 18.6% less iodine by moderate concentration contrast media (300 mgI/mL) instead of high concentration contrast media (370 mgI/mL). The 100 kVp protocol had overall better diagnostic image quality for evaluating DVT by CTV and hence could provide higher diagnostic accuracy for evaluation of DVT (51).…”
Section: Indirect Ctvmentioning
confidence: 99%
“…To overcome these limitations, Cho et al investigated the role of low tube voltage (100 kVp) setting in CTV in diagnosis of DVT and evaluated the feasibility of reducing the amount of intravenously administered contrast (51). They concluded that lower tube voltage CTV protocol showed significantly higher venous enhancement and contrast to noise ratio and image noise similar to the conventional 120 kVp protocol in spite of administering 18.6% less iodine by moderate concentration contrast media (300 mgI/mL) instead of high concentration contrast media (370 mgI/mL).…”
Section: Indirect Ctvmentioning
confidence: 99%
“…This treatment aims to prevent thrombus propagation, and to reduce the risks of PE and DVT recurrence. However, anticoagulation therapy does not possess significant fibrinolytic activity, and patients with severe, extensive and proximal DVTs remain at high risk (15). In DVT treated with anticoagulants alone, it…”
Section: Discussionmentioning
confidence: 99%